(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article focuses on the development of science, the rapid growth of production, the improvement of teaching based on artificial intelligence, the correct formation of a holistic picture of the world in the minds of school students during the educational process and finding correct solutions, and ensuring the close interconnection of fundamental knowledge with practice by improving the process of teaching natural sciences to school students based on a competency-based approach through artificial intelligence tools.